2003
DOI: 10.1046/j.1365-2583.2003.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and mapping analysis of a non‐susceptibility gene to densovirus (nsd‐2) in the silkworm, Bombyx mori

Abstract: Nonsusceptibility to Bombyx mori densovirus type 2 (BmDNV-2) is controlled by a recessive non-susceptibility gene, nsd-2 (non-susceptibility to DNV-2) in B. mori. Taking advantage of a lack of crossing over in females, reciprocal backcrossed F1 (BF1) progeny were used for linkage analysis and mapping of nsd-2 using silkworm strains C124 and 902, which are classified as being highly susceptible and non-susceptible to DNV-2, respectively. BF1 larvae were inoculated twice with DNV-2 virus at the first and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In our results, the food preference gene was found to exist on the chromosomal region between clone e73 and ep16, and the closer clone e73 was mapped at the distance of 4.2 cM. This distance is estimated as 2 Mbp at the sequence level because 1 cM corresponds to approximately 500 kbp in B. mori (Promboon et al, 1995;Abe et al, 2000;Ogoyi et al, 2003). This is an important step to obtain the most closely linked marker for cloning the food preference gene.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In our results, the food preference gene was found to exist on the chromosomal region between clone e73 and ep16, and the closer clone e73 was mapped at the distance of 4.2 cM. This distance is estimated as 2 Mbp at the sequence level because 1 cM corresponds to approximately 500 kbp in B. mori (Promboon et al, 1995;Abe et al, 2000;Ogoyi et al, 2003). This is an important step to obtain the most closely linked marker for cloning the food preference gene.…”
Section: Discussionmentioning
confidence: 56%
“…With respect to clone m112, which has been assigned to linkage group 28 using strains RF02 and RF50 (KadonoOkuda et al, 2002), Ogoyi et al (2003) reported that this clone was sorted into linkage group 27. In this study, clone m112 gave the same pattern as linkage group 27.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abe et al (1998Abe et al ( , 2000 identified and mapped several random-amplified polymorphic DNA (RAPD) markers linked to the nsd-1 and nsd-2 genes. Ogoyi et al (2003) mapped nsd-2 using the restriction fragment length polymorphism method, and obtained 3 closely linked cDNA markers. Based on a map-based cloning analysis, Li et al (2001a) identified an RAPD marker linked to nsd-Z.…”
Section: Introductionmentioning
confidence: 99%